The aesthetics of shadow : lighting and Japanese cinema - Miyao, Daisuke (Duke University Press, 2013)
By exploring the ""aesthetics of shadow"" in Japanese cinema in the first half of the twentieth century and treating cinematographers and lighting designers as essential collaborators in moviemaking, Daisuke Miyao reinterprets Japanese film history.